Вільні коливання бурильних колон, що обертаються - Гуляєв, В.І.; Луговий, П.З.; Горбунович, І.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The mathematical models are proposed for the simulation of vibrations of rotating deep drill columns. The factors of their prestressing by gravity forces and torques, the gyroscopic interaction of rotary and linear motions, and a destabilizing effect of the internal flow of a washing liquid are taken into consideration. The essential ''numerical rigidity'' of the constructed equations is found. A technique for their solution in large segments of the column length is elaborated, and a software is created. The phenomena and effects accompanying the processes of drilling in large depths are discussed.